Herakles, Jezus Chrystus i Lord Vader na rozstajnych drogach. O etycznym przesłaniu metody LEGO-LOGOS - Spychała, Jarosław Marek (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
The article is devoted to the myth of ‘Hercules at the crossroads’ and its ethical aspects. The myth was created in circles of Pythagoreans, and was kind of incentives to the right – according to the Pythagoreans – way of life. The echoes of the myth we can find in Plato’s philosophy, the life of Christ, as well as in popular movies such as Star Wars or The Matrix. The author of article adapts the myth of Hercules in their philosophical workshops ΛΕΓΩ-ΛΟΓΟΣ (LEGO–LOGOS). During the workshops ΛΕΓΩ-ΛΟΓΟΣ, participants read the texts of various philosophers: Plato’s, Aristotle’s, Cicero’s, Marcus Aurelius’, and later thinkers’: Leonardo Da Vinci’s, Descartes’ and others’. All texts are selected by a philosophical key, with a strong ethical message in the background built on the canvas of the myth of Hercules at the crossroads. This idea is presented by the author in order to illustrate its meaning with the help of classical philosophy and modern, philosophically saturated movies.